STUDI KASUS PENERAPAN RANGE OF MOTION PADA KLIEN TN. S DENGAN MASALAH GANGGUAN MOBILITAS FISIK AKIBAT STROKE NON HEMORAGIK DI KELURAHAN JATIJAJAR KOTA DEPOK - Shafa Cahya Kamila (2023)
Background: Ischemic or non-hemorrhagic stroke occurs due to a blockage in the blood vessels to the brain. This blockage is caused by a thickening of the blood vessel walls called Atheroschlerosis and blockage of blood in the brain by emboli, namely blood clots originating from thrombus in the heart. Ischemic stroke can occur by several other factors such as race, age, family history, gender. The main problem that arises in ischemic stroke, namely impaired physical mobility which greatly affects the fulfillment of ADL sufferers. This research was conducted to find out the right way of handling ischemic stroke patients with impaired physical mobility through comprehensive nursing care. Methods: This study used a case study approach to see how nurses handled Mr. S who experienced impaired physical mobility in the Jatijajar area, Depok City from February 10 to March 10 2023. Data collection was carried out by means of interviews, observation and physical examination. Results: The main nursing diagnoses on Mr. S, namely impaired physical mobility associated with neurological disorders characterized by decreased muscle strength. Nursing interventions carried out in the form of identifying muscle strength, as well as providing ROM therapy. Nursing implementation is carried out in accordance with nursing interventions that have been made and nursing evaluations are carried out. During 10 visits in 5 days, Mr. S can be partially resolved by continuing ROM therapy by the client and family. Conclusion: Nursing care given to Mr. S can be resolved and Mr. S can intervene independently